Industrial sludge as construction material - Chew, Lay Chyi. (2012)
The company, ISK-Singapore produces 100 tons of TiO2 industrial sludge per day. The sludge is send to the landfill for disposal. As the company will be expanding within the next few years, which also mean produce even more industrial sludge, this has raise two awareness, one of which is the availability of limited landfill sites and the other is the renewed interest in converting industrial sludge into construction materials. If TiO2 sludge can be reused as a construction material, it is more environmental friendly instead of disposing off at the municipal landfill. It will also mean business for the company as sludge is being reused by combining with cement to produce a construction and reclamation material. The process includes finding the best combination mixture between industrial sand and concrete to make the sludge sand and then replaced in as sand to make the grade 30 concrete. Leaching tests on heavy metals for the sludge sand using TCLP and ICP analysis showed that the leachate contaminants are within the EPA acceptable range. This report serves to inform and facilitate the reader in the results and conclusions obtained from the experiments done by the author and her partner on the usability and practicality on using ISK’s industrial sludge as a non-structural construction material.